2014
DOI: 10.1016/j.compenvurbsys.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysing hiker movement patterns using GPS data: Implications for park management

Abstract: Analysing hiker movement patterns using GPS data: Implications for park management Meijles, E.; de Bakker, M.; Groote, P.; Barske, R. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this cover page is limited to 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 27 publications
4
39
1
4
Order By: Relevance
“…To obtain trajectories from visitors, in several cases, authors provide them preconfigured GPS devices to facilitate the applicability of statical techniques within small confined areas [3,4,24]. In the analysis of the movement, several techniques are used such as point density [5,25,26], counting the frequency of visits on a determined area [6,27], identifying suspension patterns (areas with a reduction in the speed), and flow distribution among areas [3]. In these studies, the goal is to obtain a rank of areas or trail segments according to some characteristic (e.g.…”
mentioning
confidence: 99%
“…To obtain trajectories from visitors, in several cases, authors provide them preconfigured GPS devices to facilitate the applicability of statical techniques within small confined areas [3,4,24]. In the analysis of the movement, several techniques are used such as point density [5,25,26], counting the frequency of visits on a determined area [6,27], identifying suspension patterns (areas with a reduction in the speed), and flow distribution among areas [3]. In these studies, the goal is to obtain a rank of areas or trail segments according to some characteristic (e.g.…”
mentioning
confidence: 99%
“…From the transport point of view, the study of tourist movement is critical because of its possible influence on the planning of the same, to avoid congestion; and also to manage the destination's load capacity, as presented in Lew and Albrecht [41][42][43][44][45][46]. From the administration and management of a destination point of view, studies have focused mainly on the analysis of the behavior of tourists, based on information on the movement of flows [47,48]. Other works focus on information and help tourists in specific places such as natural parks, depending on the cases [49][50][51][52][53][54] or for decision-making regarding infrastructure congestion and overburden in natural areas [55][56][57][58][59][60][61][62].…”
Section: Conceptualization Of Tourist Movementmentioning
confidence: 99%
“…It has been reported that spatial behaviour within protected sites depends on the area's physical characteristics (e.g., dunes, marshes, woods) but also on the general behaviour and civic-mindedness of each society and type of users [15,23]. It appears that trespassing onto reserves or straying from designated trails is less common in some cultures [39] than in others [38]. A study by [18] noticed that user's behaviour was related more strongly to the type of user than to their socio-demographic profile.…”
Section: Constitution Of Public Usementioning
confidence: 99%